A especificação da ação afirmativa no Brasil: a experiência do centro nacional de cidadania negra em Uberaba - MG - Aguiar, Márcio Mucedula (2005)
This term paper aims to analyse the policies against discrimination and racism of the Black Citizenship National Centre, in Uberaba, State of Minas Gerais. We firmly believe that the incorporation of the myth of racial democracy and its logical ambiguity is directly related to the strategic action against racial inequality developed by this Institute. Such ambiguity can be seen from its conception of Affirmative Actions which combines specific measures for the Black and global measures for everybody, no matter their financial situation or their ethnic-racial identity. This study found out that The Black Citizenship National Centre was born and developed under the strong influence of Black´s movements and claims held at the beginning of the last century as well as their present demands. Besides that, its ambiguous perception of the racial inequalities enables the emergence of allied people from different races and financial situation who could be vital for the construction of an effective racial democracy in Brazil.